PERAN KEGIATAN EKSTRAKURIKULER KEAGAMAAN DALAM MENINGKATKAN KARAKTER PESERTA DIDIK DI SMAN 1 PAMEKASAN - Ahmad Budi Susanto; Fathurrosyid (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
Religious extracurricular activities in educational institutions are a strategic step in strengthening the religious character of students. Through these activities, students not only understand their obligations as Muslims, but are also able to practice religious teachings in their daily lives so that these religious values become ingrained in their personalities. Therefore, religious extracurricular activities play an important role as a means of forming, strengthening, and internalizing religious values in students. Based on this background, this study aims to reveal the implementation of religious extracurricular activities and the role of school members in supporting these activities as an effort to cultivate worship habits in order to strengthen the religious character of students at SMAN 1 Pamekasan. This study uses a qualitative approach with a phenomenological type. Research data were obtained from primary and secondary sources through interviews, observations, and documentation. Data analysis was conducted using an interactive model that included the stages of collection, reduction, presentation, and conclusion or verification. The results showed that religious extracurricular activities were carried out through the habit of praying in congregation, religious lectures, social activities, and religious holidays. These activities aim to foster discipline, religious enthusiasm, responsibility, and shape the personality of a perfect human being. The role of the school community includes the principal, who instills habits of worship and positive behavior in a continuous manner, and teachers, who play an active role in understanding, instilling, and motivating students to have a strong religious character.